Physicochemical Quality and Antioxidant Enhancement of Jack Bean Sauce with Pineapple Extract Addition and Different Fermentation Time - Paramita, Brigitta Laksmi; Pranata, Fransiscus Sinung; Paksi Mantara, Crispinus Devico; Pakalla, Veronika Nersy (Diponegoro University, 2025)
Jack bean (Canavalia ensiformis L.) is one of the underutilized local Indonesian commodities that has the potential to be an alternative source to substitute soybean, which has been widely used as a source of protein. High nutritional value, such as essential amino acids, kaempferol glycoside, and higher protein content, is found in this legume. There are two prominent steps in soy sauce production that promote enzymatic reactions and enhance nutritional value. The first step is fermentation involving mold such as Rhizopus sp. called koji, and the second one is fermentation in the brine solution called moromi. However, the fermentation process entails a prolonged duration. The addition of another enzyme, such as bromelain from pineapple extract, is needed to accelerate the rate of enzymatic reactions. This study aims to determine the effect of bromelain addition from pineapple extract on the physicochemical and antioxidant quality of jack bean sauce. Bromelain was extracted from pineapple, which was added in the jack bean sauce fermentation process. Jack bean was inoculated with tempeh culture (Rhizopus oryzae), incubated for 3-4 days, and added with various bromelain concentrations. Significant differences in protein content, glutamic acid content, and antioxidant activity of jack bean sauce were reported, affected by bromelain concentrations and fermentation time. Moreover, a significant difference in pH was affected by bromelain concentrations. Total soluble solids were found to be similar and not significantly different. Fermentation time for 60 days and 5% addition of bromelain was the optimum condition for jack bean sauce, which exhibited the highest content of glutamic acid, protein content, and antioxidant activity.